طرق تلقي احلديث عند الصحابة يف حياته صلى هللا عليه وسلم - Yabi, S.; Basir @Ahmad, A.; Mamat, A.; Niteh, M. Y. (Universiti Sains Islam Malaysia, 2024)
The companions realized the status and value of hadith of the Prophet Muhammad. They took in the peremptory texts and conveyed it. The Companions were truly loved and closed to the Prophet PBUH, they listen to His hadith, applied it in their lives, and conveyed it to the people after. The beholders of books of knowledge know clearly that the Companions worked hard to spread, conveyed and applied the Sunnah in the hadith from The Prophet PBUH to the next generations. Throughout the research from the related books and references established, the researcher founds that there are several methods and efforts by The Companions to receive the hadith from The Prophet PBUH. As an example The Companions diligently attend to The Prophet’s PBUH lectures to receive the hadith. There were various possibility methods such as, listened directly from the Prophet PBUH, or pointed out to them, or as a writer of the hadith, or travelled with Him. As the results from their hard works and efforts, the hadith was protected by kept it in their minds and written it in books. They understand the hadith with their mind and spread it among the people. They were also applied the hadith in every single things in their lives. The researcher will describe about these methods followed by The Companions, and The Companions’ efforts in keeping the purity of hadith from The Prophet Muhammad